2017
DOI: 10.1055/s-0043-112746
|View full text |Cite
|
Sign up to set email alerts
|

Interventionen zur Reduzierung sitzenden Verhaltens am Büroarbeitsplatz – eine systematische Literaturanalyse

Abstract: Sedentary behaviour is a health risk factor independent of physical activity. Interventions that aim to reduce sitting at the workplace are particularly important as office workers spend a large proportion of their working hours sitting. This systematic review examines whether these interventions (SB or PA interventions during work time) reduce sitting time among office workers and which variables moderate intervention effects. A systematic literature search was conducted from April to May 2016 in the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Letztere Studien sind jedoch sehr heterogen [34]. Insgesamt wird dieses auch in weiteren Übersichtsarbeiten geschlussfolgert, und der Ruf nach Studien mit längerem Nachuntersuchungszeitraum, höherer Probandenzeit und Studienqualität wird einstimmig gefordert [36,45,46].…”
Section: Konzeptionelle üBerlegungen Und Vorliegende Studien Zu Interunclassified
See 1 more Smart Citation
“…Letztere Studien sind jedoch sehr heterogen [34]. Insgesamt wird dieses auch in weiteren Übersichtsarbeiten geschlussfolgert, und der Ruf nach Studien mit längerem Nachuntersuchungszeitraum, höherer Probandenzeit und Studienqualität wird einstimmig gefordert [36,45,46].…”
Section: Konzeptionelle üBerlegungen Und Vorliegende Studien Zu Interunclassified
“…Die Heterogenität wird derzeit selten über eine fehlende Theorieorientierung diskutiert [46,47]. Dies verwundert, da theoriebasierte Interventionen durchaus eine höhere Wirksamkeit zugeschrieben wird.…”
Section: Konzeptionelle üBerlegungen Und Vorliegende Studien Zu Interunclassified
“…For example, systematic reviews of work environments have considered the relationship between desk type and heart rate, blood pressure, cardiometabolic risk factors, body mass index (BMI), work productivity, and mood (MacEwen et al, 2015), or open-plan workspaces work environments and health components such as sickness absences, job satisfaction, job concentration, work fatigue, or musculoskeletal disorders (De Croon et al, 2005;Richardson et al, 2017). Numerous studies have considered the work environment and reducing sedentary behavior at work (Becker et al, 2019;Chau et al, 2016;MacEwen et al, 2015;Neuhaus et al, 2014;Tew et al, 2015). However, no systematic reviews have focused on the relationship between physical activity and physical or structural office design components (desk, office layouts, floor plans, and building design) of the work environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, a Cochrane review concluded that evidence that sit-and-stand desks reduce sitting time at work was of low quality [18]. Further systematic reviews and meta-analyses of workplace intervention strategies argue that the combination of educational/behavioral and environmental interventions, referred to as multicomponent interventions, are the most promising for reducing sitting time [18,19,20].…”
Section: Introductionmentioning
confidence: 99%